VALUES OF RELIGIOUS TELERANCE IN THE NARRATIVES OF ASBAB NUZUL: A STUDY OF ALAL-WAHIDI’S ASBAB NUZUL AL-QUR’AN - Rahman Hakim; Ghosoun Joumaa (Universitas Kiai Abdullah Faqih Gresik, 2026)
This research aims to examine the asb?b al-nuz?l narratives in Al-W?hid?’s Asb?b Nuz?l al-Qur’?n, which describe the values of religious tolerance during the era of Prophet Muhammad SAW through the context of revelation events. Asb?b al-nuz?l is a specialized term referring to the historical events or circumstances that underlie the revelation of specific Quranic verses. The researcher investigates several asb?b al-nuz?l accounts in Al-W?hid?’s work pertaining to verses that intersect with the issue of religious tolerance. This study employs a qualitative research method using a library research approach and content analysis. The findings indicate that numerous Quranic verses have asb?b al-nuz?l backgrounds aimed at fostering harmonious religious tolerance; such as prohibiting followers from coercing others to embrace Islam and the prohibition against insulting the beliefs of other faiths.